Identifying New England’s underutilized seafood species and evaluating their market potential in a changing climate - Davis, Amanda G.; Staudinger, Michelle D.; Mills, Katherine E. (Frontiers in Marine Science, 2023)
Developing and diversifying market opportunities for lesser known yet abundant seafood species has been a successful strategy for seafood businesses in the Northeast United States. Since climate change and other stressors are currently threatening the economic vitality of New England’s seafood industry, it is important to identify if there are lesser-known species that could simultaneously support additional market opportunities and remain resilient in a warming climate. We developed a quantitative definition for the term “underutilized species’’ based on five criteria derived from science-based sustainable fishing metrics. Using this definition, we evaluated 47 stocks in the Northeast United States during the initial time period of 2013-2017 to identify seven underutilized finfish species that could be considered for new market opportunities as part of a climate-smart approach: 1) Acadian redfish (Sebastes fasciatus), 2) Atlantic pollock (Pollachius virens), 3) butterfish (Peprilus triacanthus), 4) haddock (Melanogrammus aeglefinus), 5) scup (Stenotomus chrysops), 6) silver hake (Merluccius bilinearis), and 7) white hake (Urophycis tenuis). The climate resiliency of these resulting seven species was then evaluated using a framework consisting of species-specific metrics on climate sensitivity, directionality (of responses to climate impacts) and future habitat availability under warming scenarios. Our results show that assessing underutilized species on a regular basis and evaluating their ongoing responses to climate change can be a part of a climate-smart approach towards building more diversified and adaptive markets.